Development of Eutectic Ionic Liquids as an Electrolyte in Dye-Sensitized Solar Cells (DSSCs) - MOHD FARIDZ HILMY, NURFATHIAH IZZATY (2021)
Ionic liquids (ILs) have been widely used as an electrolyte in dye sensitized solar cells (DSSCs) to replace the organic solvents due to their non-flammability, chemical and thermal stability as well as less prone to evaporation and leakage. However, some of the ILs possessed high viscosity and low ionic conductivity. Therefore, the target of this study is to develop eutectic ILs mixture as an electrolyte with low viscosity, high ionic conductivity and able to be operated at room temperature conditions. In this work, a series of eutectic ILs mixtures composed of 1-ethyl-3-methylimidazolium iodide [C2C1mim] I, 1-ethylpyridinium iodide [C2py]I, 1-propylpyridinium [C3py]I and 1-butylpyridinium iodide [C4py]I were developed and characterized as potential electrolytes in DSSCs. The eutectic ILs mixtures are mixed at different ratios to evaluate their thermodynamic behavior and physicochemical properties. The melting temperature of pure ILs and the mixtures were determined using differential scanning calorimetry (DSC) in the temperature range of 123.15 K to 393.15 K. It is found that eutectic mixtures were formed at the molar ratios of {0.75[C2py]I : 0.25[C2C1im]I}, {0.25[C2py]I : 0.75[C2C1im]I}, {0.50[C2py]I : 0.50[C2C1im]I}, {0.75[C4py]I : 0.25[C2C1im]I}, {0.25[C4py]I : 0.75[C2C1im]I} and {0.50[C4py]I : 0.50[C2C1im]I} with the latter forming a highly stable liquid with no apparent melting peak in the studied temperature range. To understand the formation of eutectic composition, a correlation between molecular structures and the interaction energies of the cations and anions of ILs was performed using Conductor-like Screening Model for Real Solvents (COSMO-RS). Dynamic viscosities of the binary mixtures and eutectic ILs electrolytes were evaluated in the temperature range of 283.15 K to 353.15 K with 10 K increments. The highest ionic conductivity was exhibited by the eutectic ILs electrolyte {0.50[C2C1im] I:0.50[C4py] I: I2 (50 wt%)} at 9.67 mS·cm−1. Further photovoltaic performance evaluation of fabricated DSSCs showed a power conversion of 0.51% short circuit current, JSC at 2.68 mA/cm2 and open-circuit voltage, VOC of 0.43 V demonstrating its potential for electrolyte application in DSSC.